Essential amino acid carbon isotope ratios as indicators of marine macrophyte response to environmental variation - Yun, Hee Young; Kim, Sangil; Choi, Hyuntae; Kim, Ji-Eun; Park, Sang Rul; Shin, Kyung-Hoon (Frontiers in Marine Science, 2024)
Introduction The carbon isotope ratios (δ13C) of essential amino acids (EAAs), including valine, leucine, isoleucine, threonine, and phenylalanine, in producers are crucial for explaining food-web structures in marine ecosystems. However, few studies have tested the variability of δ13C-EAA values in marine macrophytes, such as seagrass and macroalgae, under changing environmental conditions. Methods In this study, we examined the responses of δ13C-EAA values in macrophytes to environmental changes and explored their usefulness in characterizing macrophyte groups and local environments. We tested seagrass and macroalgae collected at different spatial and temporal scales in the field, as well as lab-cultured Ulva algae at various temperature gradients (12°C, 20°C, and 27.5°C) with additional nitrogen sources. Results We found that δ13C-EAA values in macroalgae were significantly altered by seasonality and the interactive effects of temperature and nitrogen addition in comparison with mean-centered δ13C-EAA values (normalized δ13C-EAA values relative to the mean of the overall EAAs). The δ13C-EAA values detected in macroalgae within a local environment correlated with those of a co-occurring grazer, Caprella. Based on mean-centered δ13C-EAA values, macrophyte groups were distinguishable from other group (i.e., the bacteria group) even under diverse environmental conditions. Moreover, the seagrass group did not overlap with the green and the brown macroalgal group, but overlapped considerably with the red macroalgal group. Discussion These results suggest that the macrophyte-specific mean-centered δ13C-EAA values may be fairly consistent across broad spatial and temporal scales. Despite significant variation in δ13C-EAA values, the consistency in mean-centered δ13C-EAA values among specific macrophyte groups provides valuable insight into the characteristics of local trophic bases in regions under pressure from dramatic environmental changes.